2019
DOI: 10.1016/j.cogdev.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of video pace and story realism on children’s attention and response inhibition

Abstract: This study examined the influence of the realism (realistic vs. unrealistic) and pace (slow vs. fast), in a video of an actor reading a story, on 4-year-old children's attention and response inhibition. After establishing baseline cognitive performance, 187 children watched novel videos that manipulated realism and pace, while keeping other programme features constant. Irrespective of the pace, watching the videos which presented unrealistic stories improved children's response inhibition. For attention, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…Some studies have found that computer training and using educational apps may have positive effects on EF (Diamond & Lee, 2011;Thorell et al, 2009). However, other studies found various effects on EF depending on the content of screen media use (Huber et al, 2018;Kostyrka-Allchorne et al, 2019), which was not taken into account in our study. As computers, tablets, and smartphones are often used by young children to watch movies or videos (Levine et al, 2019) Thus based on results of our study we can conclude that in typically developing preschool children from low risk and well-educated families the time of exposure to various screens is not related to their executive functions.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Some studies have found that computer training and using educational apps may have positive effects on EF (Diamond & Lee, 2011;Thorell et al, 2009). However, other studies found various effects on EF depending on the content of screen media use (Huber et al, 2018;Kostyrka-Allchorne et al, 2019), which was not taken into account in our study. As computers, tablets, and smartphones are often used by young children to watch movies or videos (Levine et al, 2019) Thus based on results of our study we can conclude that in typically developing preschool children from low risk and well-educated families the time of exposure to various screens is not related to their executive functions.…”
Section: Discussionmentioning
confidence: 63%
“…Some authors argue that the fast‐paced video content may be detrimental for children's cognitive regulatory systems as its rapidly changing sensory features capture attention in a bottom‐up fashion and voluntary attention regulation does not take place (Lillard & Peterson, ). However, these conclusions have been recently challenged by Kostyrka‐Allchorne, Cooper, and Simpson (), who found that viewing short videos featuring unrealistic events improves inhibitory control of 4‐year‐olds irrespective of the pace of the videos. Thus, there is accumulating evidence that negative effects of TV viewing on EF may be diminished in highly educated families of higher SES, where children are expected to watch age appropriate contents and still engage in other developmentally crucial activities.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported positive effects of fantastical material on children’s executive functions albeit within a short‐term design timeline. Kostyrka‐Allchorne, Cooper, and Simpson () examined the impact of pace and fantastical impact on cognition including both inhibition and attention. Their study, conducted with 3‐ to 5‐year‐olds, included a different format to previous research as video clips were of actors reading a story in contrast to a cartoon.…”
Section: Discussionmentioning
confidence: 99%
“…Lillard and Peterson (2011) demonstrated that, compared to a control group of children who were drawing, a group who watched a fast-paced cartoon performed significantly worse in a postviewing assessment of executive function, which included a measure of response inhibition. However, a recent study, which focused on measuring children's inhibition, rather than broad executive function, failed to provide evidence that pace had consequences for children's inhibitory behaviour (Kostyrka-Allchorne, Cooper, & Simpson, 2019) .…”
mentioning
confidence: 99%
“…A substantial limitation to this literature, and perhaps an explanation for the conflicting findings, is a potential confound between pace and other unmeasured features present in the commercially available cartoons. Very few studies, which examined the effects of television or video watching, used stimuli that allowed one to isolate the effects of pacing (i.e., Cooper et al, 2009;Kostyrka-Allchorne et al, 2019;Kostyrka-Allchorne, Cooper, Gossmann, et al, 2017). The paucity of research limits our current understanding of how pace in isolation affects children's post-viewing behaviour.…”
mentioning
confidence: 99%